Studies on complement systems in patients with primary biliary cirrhosis - KURODA, Masahito; MORITOH, Takao; TAKAGI, Tohru; KASUKAWA, Reiji; SAITOH, Koichi; OHBA, Takashi; NISHIMAKI, Tomoe (Kanzo, 1990)
Complement hemolytic activities (CH50, C3H50) and protein amounts of C3, C4 and split products C3d were studied in sera of patients with PBC, in which non-icteric patients were selected in order to avoid the influence of cholestasis on complement system. These complement values were considered from the points of complication of other autoimmune diseases in the patients and of granuloma in their liver. In the PBC patients without other autoimmune diseases, CH50 and C3d values were significantly higher than those of normal subjects (p<0.01), whereas C3 and C4 levels were normal. On the other hand, in the PBC patients complicated with other autoimmune diseases, CH50 levels were normal, whereas C4 levels were significantly lower than those of normal subjects (p<0.01). A positive correlation (p<0.05) between levels of C3 and C4 and also of CH50 and C3H50 were observed. In the PBC patients without other autoimmune diseases, mean levels of CH50, C3H50 and C3 of patients with granuloma in their liver were higher than those of patients without granuloma. These results would indicate that the complement system in PBC patients without other autoimmune diseases were activated through alternative pathway, whereas those in patients with PBC complicated with other autoimmune diseases were activated through classical pathway. Granuloma in the liver might be responsible for the abnormal activation of complement system.